HUBUNGAN ANTARA AKTIVITAS FISIK DENGAN DISMENOREA PRIMER PADA MAHASISWI PRODI ILMU KEPERAWATAN STIKES DI SURABAYA - Jessica Wahyu Amanda; Kurniawaty, Yuni Kurniawaty; lestarina, ni nyoman wahyu (JPK : Jurnal Penelitian Kesehatan, 2023)
Primary dysmenorrhea was menstrual pain that recured regularly since the first menstruation and was most common in women aged 20 to 30 years. Physical activity was an activity to move the body that expended energy and energy to improve health and fitness for the body. Women who lacked physical activity tend to experience dysmenorrhea. The phenomenon found by researchers in nursing student who often experienced dysmenorrhea during menstruation and did not do physical activity. The purpose of this study was to identify the relationship between physical activity and primary dysmenorrhea in nursing students. The design of this research was a correlation study with a cross section approach. The number of samples in this study amounted to 57 respondents who experienced primary dysmenorrhea taken using simple random sampling. Student physical activity was measured using the International Physical Activity Questionnaire (IPAQ) and primary dysmenorrhea was assessed by the NRS pain scale (Numerical Rating Scale). Statistical analysis using ASDPP showed that more than 50% (53%) of respondents had mild physical activity and more than 50% (53%) of respondents had moderate primary dysmenorrhea. The results of the Spearman Rank test showed that physical activity was not associated with primary dysmenorrhea with a value of p > (p = 0.079). This could be because there are other factors that might influence the occurrence of primary dysmenorrhea, one of which is stress. Researchers provided suggestions for further researchers to assess other factors that could affect the occurrence of primary dysmenorrhea